PERCEIVING AND DEALING WITH CULTURE SHOCK: THE STUDY OF CHINESE INDONESIAN-LANGUAGE STUDENTS - Qun, Wang; Syihabuddin, Syihabuddin; Mulyati, Yeti; Damaianti, Vismaia S (UPI Press, 2018)
This study reports culture shock issues such as pragmatic failures, social anxiety or loss of motivation encountered by international students, and specifically focuses on Chinese Indonesian-language students during study abroad in Indonesia. The data were collected through in-depth interviews and participant observations and were analyzed using qualitative approach. A total of eight Chinese students responded to the research that specifically stressed culture shock symptoms and the influence in respect to intercultural communicative competence. The findings put forward that students of this study had all experienced culture shock in view of intercultural communication, which could lead to inconvenience living in Indonesia. The results indicate that before entering a new cultural environment, it is very important to prepare as much beforehand as possible, especially for foreign language learners in host countries. The researcher proposed several recommendations that certain encouragement and support from teachers, media and method development from educational institutions, and a confident attitude from oneself should be provided and built as a solution for students who need to deal with culture shock problems.